Função cognitiva e qualidade de vida de pacientes com doença renal crônica nos estadios III e IV - Marchette, Juliana Cristina Nunes [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The prevalence of Chronic Kidney Disease (CKD) has been increasing progressively leading to cognitive impairment and poorer quality of life (QoL). This cross-sectional study evaluated 137 patients with CKD in stages III or IV in treatment at the Clinical Hospital of Botucatu Medical School (UNESP) in order to describe the prevalence of cognitive impairment and QoL indices and associated factors. In order to attend this purpose, were used a Sociodemographic and Clinical form, Generic Assessment Questionnaire Quality of Life - Medical Outcomes Study 36 - Item Short Form Health Survey, Mini Mental State Examination, Color Trails Test, Rey’s Auditive Verbal Learning Test, The Social Support Scale of The Medical Outcomes Study and the Beck Depression Inventory. The mean age of patients was 56.7 (±14.4) years, with 5.3 (±3.8) years of education. The mean glomerular filtration rate was 35.3 35,3 ml/min/1,73m2 (± 12.5) and 62.8% of the patients were into stage III CKD. The prevalence of cognitive impairment was 37.2 % and did not differ between the CKD stages. The QoL indices had lower averages 58.4 to 74.2. The descriptive analysis indicated no statistically significant differences in the distribution of patients in different stages of CKD. The presence of cognitive impairment was independently associated with the stage of CKD, schooling, presence of hypertension and depressive symptoms. Regarding QoL, worst rates in all areas were independently associated with the presence of depressive symptoms. Sex, age, marital status, occupation, perceived social support, presence of diabetes mellitus, urea, creatinine and hemoglobin levels influenced the quality of life, although it was not associated with all domains. Given the results of this study, a comprehensive care of patients with CKD in stages III and IV is considered important, paying attention to the factors that interfere with their QoL and levels of cognitive impairment, with special ...

A prevalência de Doença Renal Crônica (DRC) está aumentando progressivamente e seus portadores constituem população de risco para comprometimento cognitivo e pior qualidade de vida (QV). Este estudo, de corte transversal, avaliou 137 pacientes portadores de DRC, nos estadios III ou IV, em seguimento ambulatorial no Hospital das Clínicas da Faculdade de Medicina de Botucatu com o objetivo de descrever a prevalência de comprometimento cognitivo e índices de QV e fatores associados. Para tanto foram utilizados: Formulário de dados sociodemográficos e clínicos, Questionário Genérico de Avaliação de Qualidade de Vida - Medical Outcomes Study 36 Item Short-Form Health Survey, Mini Exame do Estado Mental, Teste de Trilhas Coloridas, Teste de Aprendizagem Auditivo-Verbal de Rey, a Escala de Apoio Social do Medical Outcomes Study e o Inventário de Depressão de Beck. A idade média dos pacientes foi de 56,7 (±14,4) anos, com média de escolaridade de 5,3 anos (±3,8). A taxa de filtração glomerular média foi de 35,3 ml/min/1,73m2 (±12,5), sendo que 62,8% dos pacientes se enquadravam no estadio III da DRC. A prevalência de comprometimento cognitivo foi de 37,2% e não diferiu entre os estadios. Os índices de QV apresentaram médias inferiores de 58,4 a 74,2. A análise descritiva indicou que não houve diferenças estatisticamente significativas na distribuição dos pacientes nos diferentes estadios da DRC. A presença de comprometimento cognitivo associou-se independentemente com o estadio da DRC, escolaridade, ser portador de hipertensão arterial sistêmica e sintomas depressivos. Com relação à QV, piores índices em todos os domínios se associaram independentemente com a presença de sintomas depressivos. Sexo, idade, situação conjugal, ocupação, percepção de apoio social, presença de diabetes melito, níveis de uréia, creatinina e hemoglobina influenciaram os índices de qualidade de vida, embora não tenham se ...
Keywords: Rins - Doenças; Insuficiencia renal cronica; Qualidade de vida; Equilibrio cognitivo; Comprometimento (Psicologia); Estudos transversais; Estadiamento de neoplasias; Kidneys